Zina Dalam Perspektif Hukum Islam dan Kitab Undang Undang Hukum Pidana - Kahar Muzakir (PT FORMOSA CENDEKIA GLOBAL, 2022)
Adultery is a very bad act not only in the view of Islam but also in the view of the Criminal Code. But by using the comparative analysis method found a difference between Islamiclaw and the book of law and criminal in terms define adultery aswell as legal consequences. Sexual relations between youngcouples are not categorized as adultery in the book of law andcriminal because they are not in a valid marriage bond. The bookof law and criminal also does not ensnare adultery to Article 27BW even though they are in a valid marriage bond. In addition, ifthe husband or wife of adultery gives permission to the partnerto commit adultery, then Article 284 cannot ensnare them. Whilein Islamic law perspective, any sexual relations outside a validmarriage bond is categorized as adultery.and the punishment has also been determined in the Qur'an. In the view of Islam there are two types of adultery, the first is adultery. Zina muhsan is adultery committed by people who are